2012
DOI: 10.1021/bi201575f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calcium in Metalloenzymes: Effects of Calcium Removal on the Axial Ligation Geometry and Magnetic Properties of the Catalytic Diheme Center in MauG

Abstract: MauG is a diheme enzyme possessing a five-coordinate high-spin heme with an axial His ligand and a six-coordinate low-spin heme with His-Tyr axial ligation. A Ca2+ ion is linked to the two hemes via hydrogen-bond networks, and the enzyme activity depends on its presence. Removal of Ca2+ alters the EPR signals of each ferric heme such that the intensity of the high-spin heme was decreased and the low-spin heme was significantly broadened. Addition of Ca2+ back to the sample restored the original EPR signals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…(i) The 'definition' of the dihaem redox centre of MauG should be expanded to include not only Trp 93 , but also the bound Ca 2 + . The results of the present study together with those of previous studies [16,22,23] indicate that tryptophan at position 93 and bound Ca 2 + must both be present with the two haems in order to efficiently catalyse TTQ biosynthesis. The same is likely to be true for DCCPs with respect to the reactions that they catalyse.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…(i) The 'definition' of the dihaem redox centre of MauG should be expanded to include not only Trp 93 , but also the bound Ca 2 + . The results of the present study together with those of previous studies [16,22,23] indicate that tryptophan at position 93 and bound Ca 2 + must both be present with the two haems in order to efficiently catalyse TTQ biosynthesis. The same is likely to be true for DCCPs with respect to the reactions that they catalyse.…”
Section: Discussionsupporting
confidence: 79%
“…This Ca 2 + does not readily dissociate, but was removed by treatment with chelators. The Ca 2 + -depleted MauG was not able to catalyse TTQ biosynthesis and exhibited Ca 2 + -dependent spectroscopic changes [22,23]. Trp 93 does not interact directly with the Ca 2 + , but forms a hydrogen bond with Asn 66 , one of ligands of Ca 2 + [8].…”
Section: Figure 1 Role Of Maug In Ttq Biosynthesismentioning
confidence: 98%
“…This Ca 2+ does not readily dissociate from MauG; however after Ca 2+ removal by extensive treatment with chelators, MauG is no longer able to catalyze TTQ biosynthesis and exhibits altered absorption, resonance Raman and EPR spectra (41, 47). The circular dichroism spectra of native and Ca 2+ -depleted MauG are essentially the same, consistent with Ca 2+ -induced conformational changes involving domain or loop movements rather than general unfolding or alteration of secondary structure.…”
Section: Structure-function Studies Of Maug and Premadhmentioning
confidence: 99%
“…It was shown that in the Ca 2+ -depleted MauG the original high-spin heme is converted to low-spin, and the original low-spin heme exhibits a change in relative orientations of its two axial ligands. EPR and Mössbauer spectroscopic results (47) show that the two hemes are present as unusual highly axial low-spin (HALS)-like hemes (48, 49) in Ca 2+ -depleted MauG, with a smaller orientation angle between the two axial ligand planes. The effects of Ca 2+ -depletion are completely reversible.…”
Section: Structure-function Studies Of Maug and Premadhmentioning
confidence: 99%
“…Removal of this Ca 2+ by chelators yields a Ca 2+ -depleted MauG which has no TTQ biosynthesis activity [11]. This is due to changes in the diheme site which prevent formation of the bis-Fe IV state [12]. Whereas addition of H 2 O 2 to native MauG generates the bis-Fe IV state, the hemes of Ca 2+ -depleted MauG are not reactive towards H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%